UNDERGRADUATE STUDENTS’ READING INTEREST AND READING COMPREHENSION OF TRIDINANTI UNIVERSITY PALEMBANG - W Wilda; Ridha Ilma (Didascein : Journal of English Education, 2020)
Reading comprehension is an active thinking process that is depended not only comprehension skill but the students’ experience and prior knowledge comprehension involves understanding the vocabulary, seeing the relationship among words and concept making judgment and evaluating. The study was aimed to find the significant correlation and contribution between reading interest and reading comprehension. Fifty four students of Undergraduate EFL students of Tridinnati University Palembang became the sample of the study. The data was gained from students’ reading interest questionnaire and their reading comprehension test. In analyzing the data, correlation analysis and regression analysis were used. The result showed that the correlation coefficient level between reading interest and reading comprehension was 0.477 with the sig. value 0.000, it means that there was a significant correlation between reading interest and reading comprehension of undergraduate EFL students Tridinanti University Palembang. Then, reading interest gave contribution to reading comprehension as much as 18.6%.Key words: reading interest, reaing comprehension.